Irmandade do Senhor Bom Jesus dos Passos: festas e funerais na Natal oitocentista - Pontes, Annie Larissa Garcia Neves (2008)
The various Religious Brotherhoods created in Brazil during Colonial and Imperial periods had as model the similar Portuguese organizations, spread out since Middle Ages. These organizations are destined to promote the cult to one devoted saint, and in accordance with a basis of solidarity and sociability, they created a matrix of auto-aid and assistance that spread out, assuming proper characteristics in each historical context where each one of them was build. The religious brotherhoods were created between sacred and profane, and their ideals were the fraternal communion and the public cult increasing, bringing together body and spiritual necessities. The historiographical analysis of the party considers the field where ritualizations of festive commemorations occurs and sustains the existence of human being, a time that does not exists without reference to the past or the memory. The study of the party itself confers, thus, the opening of present times to the past, under a kind of a new and regenerable time. In the party there s a relation of education and learning that allows the men to know certain time dimensions that they fears and there s unknown for them: through the party men would learn to domesticate the past towards repetition and the future for the expression of hopes. Paradoxically, the suspension that the party carries through in the usual time would allow to men be sensible to time continuity. They were constituted also to answer to religious and beneficent purposes, stand by a mutual aid discourse, frequently don t having any distinction between religious or social interests. Understanding the proper ritual of the processions and funeral rites as an education practice of a Tridentine Biblical History full of Christian dogmas, based upon an Iberian and baroque matrix, this work is linked to the Universidade Federal da Paraíba History s Graduate Program research line History Teaching and Historic Knowledge , intending to discuss History and Historical Culture of the XIX in Natal, Rio Grande do Norte Province capital, with special focus on imaginary that surrounds the universe of religious brotherhoods in that city, taking as object the Brotherhood of Our Lord Good Jesus of Steps, and the parties and funerals organized by and for their brothers, including the analysis of its last wills.